Pengaruh Flexible Working Space dan Organizational Culture Terhadap Produktivitas Kerja: Literature Review Manajemen Sumber Daya Manusia - Agus Suyatno; Ferdy Leuhery; Jati Wahyono Agustinus; Fatimah Malini Lubis; Muhammad Ade Kurnia Harahap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Flexible Working Space is not synonymous with working from home (WFH). FWS is a very flexible space that can be done anywhere, anytime and according to the needs and conditions that support the implementation of work. The purpose of this study is to see the effect of Flexible Working Space and Organizational Culture on Work Productivity. The method in this article is a qualitative method with literature study or Library Research. The purpose of this article is to analyze existing theories by looking at their comparison with previous theories in the research literature. The literature used is literature from research results or reviews that are emphasized in national and international scientific articles related to financial management. The results showed that (1) Flexible Working Space affects Work Productivity. (2) Organizational Culture affects work productivity. Keywords: Flexible Working Space, Organizational Culture, Work Productivity